Blumenberg’s rethoric as the art of delaying - González-Cantón, César (Ekstasis: Revista de Hermenêutica e Fenomenologia, 2013)
DOI: http://dx.doi.org/10.12957/ek.2013.7367 In this paper, I attempt to underline the ontological role of rethoric in Blumenberg’s philosophic proposal by examining one of the aspects of human temporality: that of human being’s neccessity of ‘taking their own time’. I trace back this ‘need for delaying’, structural to human beings, to its anthropological roots in instinct reduction, while attempting at the same time to highlight the relation between this anthropological level of biological ‘poverty’ and the ontological one of ‘metaphysisches Skeptizismus’.